Grafis Lingkungan: Inovasi Desain Tempat Pembuangan Sampah Sebagai Identitas Visual Taman Kunang-Kunang - Wulandari, Sri; Rizqi, Azmi Annur; Ayuswantana, Alfian Candra (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2024)
Surabaya as the 2nd largest city in Indonesia besides having great job mobility, there are tourism destinations that are no less abundant and developed. It is an attraction for tourists to visit. One of the tourist destinations in Surabaya is Taman Kunang-Kunang, located on Jalan Penjaringan Timur, Kec. Rungkut, Surabaya. Taman Kunang-Kunang has aesthetics and complete facilities. However, one of the facilities has an ordinary impression and does not represent the beauty of Taman Kunang-Kunang, namely the garbage dump. Therefore, it is necessary to strengthen the form and visual graphics of an attractive landfill environment that can reflect and improve the visual identity of Taman-Kunang-Kunang. This strengthening uses qualitative descriptive data analysis techniques with observation and literature study methods. It was found from the data analysis that the uniqueness of Taman-Kunang-Kunang, namely the firefly installation, became a reference for strengthening the shape and visual graphics of the landfill environment to improve the visual identity of the park. Maintaining the graphics of the garbage dump environment derived from the deformation of the shape of fireflies can increase the visual identity of the Fireflies Park which attracts visitors' interest and desire to dispose of garbage in its place.